2002
DOI: 10.1290/1071-2690(2002)038<0493:tgoeci>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Growth of Endothelial Cells in the Microgravity-Based Rotating Wall Vessel Bioreactor

Abstract: We characterized bovine aortic endothelial cells (BAEC) continuously cultured in the rotating wall vessel (RWV) bioreactor for up to 30 d. Cultures grew as large tissue-like aggregates (containing 20 or more beads) after 30 d. These cultures appeared to be growing in multilayers around the aggregates, where single beads were covered with confluent BAEC, which displayed the typical endothelial cell (EC) morphology. The 30-d multibead aggregate cultures have a different and smoother surface when viewed under a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…74,75 The horizontally rotating bioreactors, or slowturning lateral vessels, were designed as a rotating cylinder of culture medium, with a gas-permeable membrane for oxygen and carbon dioxide exchange, and fittings for sampling or medium exchange. 75,76 The speed of the rotation could be controlled to match the settling velocity of the tissue constructs, keeping them suspended within the vessel.…”
Section: Rotating Bioreactorsmentioning
confidence: 99%
“…74,75 The horizontally rotating bioreactors, or slowturning lateral vessels, were designed as a rotating cylinder of culture medium, with a gas-permeable membrane for oxygen and carbon dioxide exchange, and fittings for sampling or medium exchange. 75,76 The speed of the rotation could be controlled to match the settling velocity of the tissue constructs, keeping them suspended within the vessel.…”
Section: Rotating Bioreactorsmentioning
confidence: 99%
“…In the case of endothelial cells, conflicting results are reported (Carlsson et al 2003;Cotrupi et al 2005;Sanford et al 2002;Morbidelli et al 2005). While HUVEC and bovine aortic endothelial cells proliferate faster in simulated microgravity than in normal conditions (Carlsson et al 2003;Morbidelli et al 2005), porcine aortic endothelial cells engineered to overexpress vascular endothelial growth factor-receptor 2 are induced to apoptosis in modelled microgravity (Morbidelli et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Their concept based on previous observations showed that the culture of endothelial and epithelial cells under microgravity could self-organize into structures resembling native tissues. [102][103][104][105]. Although their results showed differentiated cell-types and villus-like structures, the mesenchyma was absent.…”
Section: Tissue Engineering Small Intestine (Tesi)mentioning
confidence: 96%